2010
DOI: 10.1089/ped.2010.0008
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease in Children Older Than 2 Years

Abstract: The spectrum of childhood interstitial lung diseases (chILD) encompasses a group of heterogeneous, rare disorders in children characterized by diffuse pulmonary infi ltrates and disordered gas exchange. Whereas the disorders that present in early life are unique to children, those that present in older children are also seen in adults. This review will concentrate on chILD presenting in children older than 2 years of age with a focus on the idiopathic interstitial pneumonias, connective tissue diseases, alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 51 publications
1
44
1
4
Order By: Relevance
“…Hypersensitivity pneumonitis is uncommon in childhood but manifests in an identical manner to, and shares the CT features of, the adult form of the disease. Precipitating exposures include avian antigens, mold spores, and airborne compounds from paints, glues, and insecticides (49). A German study of 23 children (aged 4-15 years) with hypersensitivity pneumonitis demonstrated poorly defined centrilobular nodules in 96% and diffuse ground-glass opacification in 73% in the acute phase (50) (Figs 20, 21).…”
Section: Disorders Related To Environmental Agents-mentioning
confidence: 99%
“…Hypersensitivity pneumonitis is uncommon in childhood but manifests in an identical manner to, and shares the CT features of, the adult form of the disease. Precipitating exposures include avian antigens, mold spores, and airborne compounds from paints, glues, and insecticides (49). A German study of 23 children (aged 4-15 years) with hypersensitivity pneumonitis demonstrated poorly defined centrilobular nodules in 96% and diffuse ground-glass opacification in 73% in the acute phase (50) (Figs 20, 21).…”
Section: Disorders Related To Environmental Agents-mentioning
confidence: 99%
“…Recently, patients with NEHI syndrome have been diagnosed using clinical findings, CT scan, infant pulmonary functions and negative findings on bronchoscopy in some centers [19]. However, despite gains in recognizing the classic clinical phenotype of NEHI, some children present with atypical clinical phenotypes that may require lung biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Birds, pets, and molds are the most common precipitating agents in children. Other causes include highly reactive lowmolecular-weight compounds in spray paints, epoxy resins, glues, and insecticides, as well as drugs such as methotrexate (Vece and Fan 2010). There is a mean lag time of 11 months from symptom onset to diagnosis, and a meticulous environmental exposure history is a crucial step in the clinical evaluation.…”
Section: Hypersensitivity Pneumonitismentioning
confidence: 99%
“…CXRs are limited in sensitivity, being normal in over one-third of cases at initial presentation (Buchvald et al 2011). The absence of serum-precipitating antibodies does not exclude the diagnosis (Clement et al 2010;Vece and Fan 2010). A presumptive diagnosis without biopsy can be made in children with an exposure history and positive precipitins, lymphocytosis on BAL, and typical findings on CT (Vece and Fan 2011).…”
Section: Hypersensitivity Pneumonitismentioning
confidence: 99%